Color conversion using Quantum Dots on high-brightness GaN LED arrays for display application. Issue 1788 (2015) - Sanchot, Audrey; Consonni, Marianne; Le Calvez, Stéphanie; Robin, Ivan C.; Templier, François
ABSTRACT: We have demonstrated the color conversion of blue micro-LEDs by means of QDs. In this paper, we will present characterizations that highlight this phenomenon. We already obtained conversion with a complete disappearance of the blue incident signal and a strong color saturation from deep blue (x=0, 1626; y=0, 0144) to deep red (x=0, 6743; y=0, 3244).